Vitamin D deficiency impairs rituximab-mediated cellular cytotoxicity and outcome of patients with diffuse large B-cell lymphoma treated with but not without rituximab. - Bittenbring, J. T.; Neumann, F.; Altmann, B.; Achenbach, M.; Reichrath, J.; Ziepert, M.; Geisel, J.; Regitz, E.; Held, G.; Pfreundschuh, M. (J Clin Oncol, 2014)
PURPOSE: To investigate the impact and mechanisms of vitamin D deficiency (VDD) on the outcome of elderly patients with diffuse large B-cell lymphoma (DLBCL). PATIENTS AND METHODS: Three hundred fifty-nine pretreatment 25-hydroxyvitamin D3 (25[OH]D3) serum levels from the RICOVER-60 study (Six Versus Eight Cycles of Biweekly CHOP-14 With or Without Rituximab in Elderly Patients With Aggressive CD20+ B-Cell Lymphomas) and 63 from the RICOVER-noRTh study (an amendment to the RICOVER-60 study in which patients received six cycles of cyclophosphamide, doxorubicin, vincristine, and prednisone administered at an interval of 2 weeks plus two cycles of rituximab [R-CHOP-14], but without radiotherapy) were determined by chemoluminescent immunoassay. Rituximab-mediated cellular cytotoxicity (RMCC) was assessed by lactate dehydrogenase release assay of CD20+ Daudi cells. RESULTS: RICOVER-60 patients with VDD (</= 8 ng/mL) and vitamin D levels more than 8 ng/mL treated with rituximab had 3-year event-free survival (EFS) of 59% and 79% and 3-year overall survival (OS) of 70% and 82%, respectively. These differences were significant in a multivariable analysis adjusting for International Prognostic Index risk factors with a hazard ratio (HR) of 2.1 (P = .008) for EFS and 1.9 (P = .040) for OS. EFS was not significantly different in patients with vitamin D levels </= 8 or more than 8 ng/mL (HR, 1.2; P = .388) treated without rituximab. This was confirmed in an independent validation set of 63 RICOVER-noRTh patients. RMCC increased significantly (P < .001) in seven of seven individuals with VDD after substitution and normalization of their vitamin D levels. CONCLUSION: VDD is a risk factor for elderly patients with DLBCL treated with R-CHOP. That VDD impairs RMCC and substitution improves RMCC strongly suggests that vitamin D substitution enhances rituximab efficacy, which must be confirmed in appropriately designed prospective trials addressing VDD and substitution not only in DLBCL, but also in malignancies treated with other antibodies, of which the major mechanism of action is antibody-dependent cellular cytotoxicity (eg, trastuzumab in breast cancer and cetuximab in colorectal cancer).
Keywords: Aged; Aged, 80 and over; Antibodies, Monoclonal, Murine-Derived/administration & dosage/*therapeutic use; Antineoplastic Agents/administration & dosage/*therapeutic use; Antineoplastic Combined Chemotherapy Protocols/administration & dosage; Calcifediol/blood; Cyclophosphamide/administration & dosage; Doxorubicin/administration & dosage; Female; Humans; Lymphoma, Large B-Cell, Diffuse/*drug therapy; Male; Middle Aged; Prednisone/administration & dosage; Risk Factors; Rituximab; Treatment Outcome; Vincristine/administration & dosage; Vitamin D Deficiency/*complications